Strengthening Micro-enterprises and Resilience Transformation (SMART) through the Establishment of the Merah Putih Cooperative in Jatisari, Bekasi - Sulistyanto, Tri Hadi (CV Media Inti Teknologi, 2025)
Background of study: Community service is a concrete manifestation of the Tri Dharma of Higher Education, emphasizing the active role of university lecturers in empowering local communities. In Kelurahan Jatisari, Kecamatan Jatiasih, Kota Bekasi, local SMEs face challenges due to the absence of a cooperative as a collective economic institution to support access to training, mentoring, and financing.Aims and scope of paper: This paper aims to examine the strategic role of WIKARA Business School (WBS) lecturers in facilitating the establishment of the Merah Putih Cooperative as a means to strengthen local economic institutions. Specifically, the community service activity analyzes the process of designing the cooperative’s organizational structure and evaluates the implementation of a digital approach to leader selection as an innovation in community-based economic empowerment.Methods: The activity applied the SMART framework through a participatory approach. WBS lecturers facilitated socialization, structured the cooperative, and organized digital leader selection using video presentations and online scoring based on eight criteria, ensuring transparency and efficiency.Result: A total of 11 candidates submitted video presentations and were assessed based on eight criteria using a digital scoring system. The process resulted in the election of 2 individuals as Chairperson and Vice Chairperson, supported by 3 additional management members. The digital evaluation demonstrated efficiency, transparency, and increased community participation.Conclusion: This program successfully established a collective economic institution and demonstrated the practical application of digital technology at the community level. It also shows that collaboration between Higer Education institution and communities can yield relevant and sustainable empowerment innovations.